Detection of diisocyanates in nesting material associated with mortality in pigeon chicks. (March 2014) - Mukai, Motoko; Woods, Leslie W.; Stump, Samuel; Ebel, Joseph G.; Levitt, Ariana S.; Frey, Margaret W.; Smith, Jeanne; Uzal, Francisco A.; Poppenga, Robert H.; Puschner, Birgit
Diisocyanates, commonly used in the production of polyurethane foams, paints, elastomers, varnishes, and coatings, are considered among the most hazardous inhalation toxicants. The present report describes 2 unusual cases of mortality in pigeon chicks associated with nesting material contaminated by diisocyanates. Case 1 was submitted by a racing pigeon breeder who had lost all the hatchlings ( n = 125) following replacement of the nesting material with a different lot. All adult birds appeared healthy, and hatchability was not significantly affected, but hatchlings became lethargic and dyspneic after a day of hatch. At necropsy, dark wet lungs were found in the hatchlings. Case 2 was submitted by a show-roller pigeon breeder. In this case, the owner reported lower hatchability, and all hatchlings (approximately 100) died within 2 days of hatching with clinical signs similar to the first case. Necropsy did not reveal any significant findings. For both cases, nesting materials were screened for toxic compounds using gas chromatography–mass spectrometry. Toluene-2, 4-diisocyanate (approximately 190–290 ppm) and 4, 4′-methylene diphenyl diisocyanate (unquantified) were detected in the nesting pads. While there is very limited information on toxicosis in birds, there are reports of inhalant exposure of diisocyanates causing pulmonary edema and death in various mammalian species. Although cause–effect relationship of mortality and the nesting material was not established in the present cases, the presence of toxic compounds in the nesting materials is a cause for concern. Further investigation is needed to determine the prevalence and toxicity of diisocyanates-contaminated nesting material in avian species.